Quantifying Phosphorus and Water Demand to Attain Maximum Growth of Solanum tuberosum in a CO2-Enriched Environment - Yi, Yan; Sugiura, Daisuke; Yano, Katsuya (Frontiers in Plant Science, 2019)
Growth promotion by ambient CO2 enrichment may be advantageous for crop growth but this may be influenced by soil nutrient availability. Therefore, we quantified potato (Solanum tuberosum L.) growth responses to phosphorus (P) supply under ambient (a[CO2]) and elevated (doubled) CO2 concentration (e[CO2]). A pot experiment was conducted in controlled-environment chambers with a[CO2] and e[CO2] combined with six P supply rates. We obtained response curves of biomass against P supply rates under a[CO2] and e[CO2] (R2 = 0.996 and R2 = 0.992, respectively). A strong interaction between [CO2] and P was found. Overall, e[CO2] enhanced maximum biomass accumulation (1.5-fold) and water-use efficiency (WUE) (1.5-fold), but not total water use. To reach these maxima, minimum P supply rate at both [CO2] conditions was similar. Foliar critical P concentration (i.e., minimum [P] to reach 90% of maximum growth) was also similar at nearly 110 mg P m−2. Doubling [CO2] did not increase P and water demand of potato plants, thus enabling the promotion of maximum growth without additional P or water supply, but via a significant increase in WUE (9.6 g biomass kg−1 water transpired), presumably owing to the interaction between CO2 and P.